Pelaksanaan Pendaftaran Pasien Lansia di UPT Puskesmas Belusuh - ningsih, Eka rahma; Dedi Uskar; Muhammad Zaini (Universitas Muhammadiyah Sidaorjo, 2023)
section. Based on the observation results of the preliminary study, the number of patient registration officers is still lacking, the policy implementation of the elderly patient registration flow has not run well and the lack of facilities and infrastructure to support services for elderly patients. This study aims to find out the general overview of the implementation of the registration flow of elderly patients at the Belusuh Health Center. The design of this study uses a qualitative descriptive method, the approach used is a method through interviews and observation with checklist tools. The sampling technique was by the purposive sampling method, with a total of 5 respondents. The results of the research were obtained in the implementation of the service flow for elderly patients at the Velusuh Health Center from the aspect of Human Resources, namely the lack of the number of officers and there are no officers with a background in medical record education in the patient registration section, the Standard Operating Procedure (SOP) already exists but the flow implemented still requires evaluation and the lack of facilities and infrastructure to support services for elderly patients. The results of the study show that the implementation of the elderly patient registration flow is seen from Human Resources, policies and facilities and infrastructure that support elderly patient registration services are still lacking and need to be evaluated.